Spatial and Perceptual Evaluation of Architectural Facade Projections and Pedestrian Walkability within Bhaktapur’s Traditional Streetscape - Maharjan, Srija; Uprety, Sanjaya (Journal of Engineering Issues and Solutions, 2026)
Balconies, overhangs, windows, colonnades, architectural trims, oriels, and brick cornices are characterized by closely spaced building with projecting elements that define Bhaktapur’s ancient streets. The facade projection influence both the pedestrian walking experience and the spatial character of streets. This study examines how architectural facade projections affect pedestrian walkability in four major traditional streets of Bhaktapur. The study examines how architectural facade projections affect pedestrian walkability and compares observed physical streetscape characteristics with pedestrian perception in four major traditional streets of Bhaktapur. The study investigates how façade projections influence important walkability characteristics such as imageability, enclosure, transparency, street interface, and pedestrian infrastructure. The study uses a mixed-method approach. Serial Vision analysis is used to observe physical streetscape characteristics, while pedestrian perception surveys are conducted to understand people’s experiences. The Relative Importance Index (RII) approach is used to analyze and rank pedestrian responses based on their walking experiences. Physical aspects such as street width and building height are considered alongside human perceptions of comfort, safety, and visual attraction. The findings show that spatial analysis and pedestrian perception produce different results. While Serial Vision analysis identifies Street 4 as the most walkable based on physical attributes (total coverage up to 86.54%), the RII results identify Street 1 as the most walkable based on user perception (RII = 2.03–2.12). Imageability emerges as the most influential attribute in both methods, while transparency is valued more strongly in perception than in spatial analysis. The results shows that pedestrian perception of walkability differ from those of the theoretical method. This divergence suggests that physical observations of streets may not fully reflect how people perceive walking in the space. The study demonstrates that walkability in traditional streets is shaped by the interaction between spatial characteristics and user perception rather than by physical form alone. The findings are important for urban designers, planners, and researchers interested in pedestrian-friendly street design, highlighting the need for integrated approaches that combine spatial analysis and perception-based evaluation.